The use of in situ Gamma-Ray Spectrometry to Assess the Environmental Impacts of Intensive Agriculture in terms of Geochemical Mobility in soil and waters - Casagrande, Matheus Felipe Stanfoca [UNESP]; Moreira, César Augusto [UNESP]; Furlan, Lucas Moreira [UNESP]; Rosolen, Vania [UNESP] (Universidad Nacional Autonoma de Mexico, 2024)
The concentration and mobility of metals in the lithosphere and hydrosphere are led by many physical-chemical parameters and processes from natural and anthropogenic origins, the last one resulting in impacts over many ecosystems around the World, including wetlands. These transitional zones, often characterized by the presence of hydric soils, adapted vegetation, and seasonal or permanent presence of surface water, are commonly under human pressure in terms of land use conversion and contamination, notably in agricultural production areas, where excess of nutrients/organic matter, pesticides, salts, sediments, heavy metals and radionuclides (originated from inorganic fertilizers) can substantially alter the ecological balance of those ecosystems. Thus, this study aimed to evaluate the agricultural impact over a tropical geographically isolated wetland in the Brazilian Cerrado by the analysis of geochemical mobility and interaction between surface and groundwater through in situ gamma-ray spectrometry and hydraulic conductivity measurements. The results demonstrated that the margins of this diabase-derived soil wetland are one of the most important and critical compartments due to its capacity of metal immobilization and surface water infiltration, indicated especially by uranium concentrations. Thorium, in turn, was most related to colluvial transport from slopes to the center of wetland. It was also corroborated by low hydraulic conductivity zones as a result of soil compaction due to heavy agricultural machinery and increase in runoff fluxes. Thus, this methodology could be used as an initial fast screening method in wetlands under other climatic and geological/pedological contexts to evaluate the local hydrogeochemical dynamics and impacts of agriculture.
Keywords: contamination; hydraulic conductivity; hydrology; thorium; uranium; wetland